The language of Art : inquiry-based studio practices in early childhood settings - Pelo, Ann. (St. Paul, MN : Redleaf Press, 2007)
Advocating practices backed by a strong theoretical framework, [this book] provides: advice on setting up a studio space for art and inquiry in your early childhood classroom or family child care home ; fifteen studio explorations on topics such as texture, color, and sculpting, designed to help children begin to develop fluency in art ; suggestions for documenting children's developing fluency with art media and its use in inquiry ; guidelines, with illustrative stories, for using a child's newfound ability as a tool for investigation".
Keywords: Art -- -- Study and teaching (Early childhood).; Reggio Emilia approach (Early childhood education).